ANALISIS PEREKRUTAN DAN SELEKSI TENAGA KERJA DI PT. ‘TORAY’ ISTEM - Sahat Sinambela; Daniel Sembiring (Faktor Exacta, 2011)
This research comprise about procedure select and acceptance of employees and also procedure orient and training work applied by field is PT. ' TORAY' ISTEM Tangerang. Rekrutmen is seeking effort a number of certain up to standard labour candidate in number to be done in and by an company. Procedure scope select and acceptance of PT employees. ‘TORAY’ ISTEM define responsibility and activity part of personnel since entry of request of labour from entire/all part of up to work agreement hand sign. In executing its activity of personnel will pursuant to at human resource planning which have been determined previously. From existing job/activity source of power categorized in two faction, that is: internal source and source of eksternal. Things influencing recruitment is employees status, opportunity of promotion, specification of work, recruitment method, regulation of labor, company solidarity, offer of labour. Selection is first effort which must be done/conducted by company to obtain;get employees which with quality and have competence to to take hold of and also partake share in doing all work at the company. Selection executed with a view to get coherence about efficiency, personality, boldness or data considered necessary to get reliable labour. While for the construction of employees in order to meningakatkan of[is quality of PT employees. ‘TORAY’ ISTEM orient and training work field to new employees and give some training type Keywords:recruitment, selection, labour.